Teknik Instruksional Pertanyaan Guru Di Tahap Evaluating Data, Driving A Conclusion, Presenting The Project In Class As Preffered & Discussion Project Based Learning Untuk Meningkatkan Skor Valid Relationship Concept Map - Rahayu, Yacinta Arum Dwi; Rinanto, Yudi; Widoretno, Sri (Universitas Sebelas Maret, 2018)
This research aimed to calculate the valid relationship score of concept map (CM) using instructional technique of teacher’s questions in the stages of evaluating data, driving a conclusion, presenting the project in class as preferred & discussion project-based learning. This research was a classroom action research. This research was a classroom action research with the research subject of 36 students in X MIPA of Senior High School. The research procedure was including: planning, lesson plan completed with assessment, acting, observing and reflecting. Validity test in this research was using triangulation method that consisted of verification of valid relationship CM score, documentation based on expert CM and interview to present the valuable relation between concepts. Reduction done to choose the data completion, data interpretation and conclusion based on the complete valid relationship data. Data analysis was using descriptive qualitative. The result of this research shows that valid relationship score of expert CM in pre-research, cycle I and cycle II were written as follows. 1.95%-14.98% with 13.89% of the under averaged students’ score and 11.11% of the over averaged students’ score. 3.08%-61.54% with 19.44% of the under averaged students’ score and 11.11% of the over averaged students’ score. 16.58%-32.16% with 11.11% of the under averaged students’ score and 16.67% of over averaged students’ score. Thus, the use of instructional technique of questioning in the stages of evaluating data, driving a conclusion, presenting the project in class as preferred & discussion project-based learning improving the valid relationship CM score on the individual and classical.